Oscillatory "Temporal Sampling" and Developmental Dyslexia: Towards an Over-Arching Theoretical Framework - Marie Lallier (Frontiers Research Topics, 2015)
Children with developmental dyslexia fail to acquire efficient reading and spelling skills despite adequate tuition and an absence of overt sensory and/ or neural deficits. Learning to read and spell requires linguistic skills, auditory skills and visual skills. Oscillatory 'temporal sampling' theory links the development of sensory and linguistic processes. The auditory system 'samples' acoustic information at different temporal rates, which for speech processing suggests that temporal information encoded by delta, theta and gamma oscillations is bound together in the final speech percept. Temporal sampling theory proposed a possible deficit in dyslexia in auditory sampling of the speech signal at syllable-relevant rates (< 10 Hz, delta and theta). This would hypothetically affect prosodic development prior to reading and syllable-based parsing, which would affect efficient linguistic skills and consequently reading development across languages. The visual system also samples information in the visuo-spatial field. In theory atypical visual oscillatory sampling could therefore be related to some of the visual features of developmental dyslexia. In this special issue, we bring together visual and auditory sensory processing studies around the general theme of oscillatory temporal sampling. Contributors were encouraged to discuss their findings within a temporal sampling perspective. The resulting studies cover a wide range of sensory processes, with findings both supporting and contradicting the theory. It is also important to note that studies covered a wide range of languages, and that the behavioural manifestations of a sampling impairment may differ both with language and over the course of development. Nevertheless, it is encouraging to see such diverse findings considered within a single theoretical framework, even if at the same time, it is apparent that an over-arching theoretical framework encompassing both visual and auditory deficits in dyslexia is yet to be achieved.